Recent Turmoil in Emerging Markets and the Behavior of Country-Fund Discounts : Renewing the Puzzle of the Pricing of Closed-End Mutual Funds - Kramer, Charles (IMF Working Papers; Working Paper ;, 1995)
This paper argues that recent movements in closed-end emerging markets funds present a strong challenge to the leading explanations of the behavior of closed-end country fund prices. In particular, closed-end funds dedicated to Mexico and other Latin American stock markets developed large premia after the December 1994 devaluation of the Mexican peso and the subsequent financial crisis. The so-called 'investor sentiment hypothesis' could explain these events only by suggesting that investors became very optimistic about emerging markets stocks, and especially Mexican stocks; this possibility seems unlikely given the facts surrounding the devaluation. We argue instead that a sensible explanation for recent dynamics of closed-end country funds is that investors in these funds are loss-averse, implying that they do not want to realize paper losses on their closed-end fund shares. This works to put a drag on the downward movement in closed-end fund prices.